Stereodynamics lectures given at a Summer School of the Centro Internazionale Matematico Estivo (C.I.M.E.) held in Bressanone (Bolzano), Italy, June 2-12, 1971 - C.I.M.E. Summer School Bressanone, Italy) (1971; Grioli, G. (Giuseppe) (Heidelberg, Germany Springer Berlin, 2011)
G. Grioli: Particular solutions in stereodynamics. P. Hagedorn: On the converse of the Lagrange-Dirichlet stability theorem. M. Langlois: Contribution à l étude du mouvement du corps rigide à n dimensions autour d un point fixe. E. Leimanis: Some recent results concerning the motion of a rigid body about a fixed point. H. Price: A canonical form of Eulers equations and a method of solutions for arbitrary applied couples. V.V. Rumyentsev: Dynamics and stability of rigid bodies. J. Wittenburg: The dynamics of systems of coupled rigid bodies. A new general formalism with application
Keywords: Dynamics, Rigid